Dimensiones de la gastronomía local en la segmentación del turismo cultural gastronómico del cantón Portoviejo- Ecuador - Cusme Sánchez, Gema Yamileth (2022)
The objective of the work was to identify the dimensions of local gastronomy that allow the segmentation of gastronomic cultural tourism in Portoviejo-Ecuador canton. A mixed character research was used with an exploratory-non-experimental approach, the methodological design is comprised of three phases. First, a tourist diagnosis was made where sociocultural, environmental, economic characteristics and basic service infrastructures were obtained that allowed knowing the current situation of the area, said information was summarized in a SWOT matrix, resulting in the non-existent gastronomic segmentation as the main weakness. The second phase included the evaluation of the gastronomic offer, through the tourist cadaster, 218 restoration services were identified, 8 traditional food establishments were characterized, establishing that the ingredients and the conservation of the recipes contribute to the gastronomic potential of the city, also applied interviews with entrepreneurs and the tourism department to determine the offer of gastronomic services. Through a bibliographic review, evolution, innovation and food inventory (15 dishes) were considered as pillars of gastronomy, implying that they are mechanisms used to improve the activity; the gastronomic dimensions were also identified through a documentary review (safety, artistic, commercial, authentic and traditional) resulting in characteristics taken into account since the granting of UNESCO. In the third phase, a survey was applied to tourists to find out their gastronomic motivations; statistical research revealed two types of segments (nutritious and authentic) visiting Portoviejo, each employing different gastronomic evaluations.